Use of Indoor Location Technologies in Healthcare Contexts: A Scoping Review - Erik Teixeira Lopes; Derek Chaves Lopes; Gustavo Pedrozo; Igor Oliveira Alves; Gustavo Alan Käfer; Pedro Henrique Santos de Medeiros; Bruno S. Gonçalves; Sérgio Eduardo Soares Fernandes; Rui M. Lima (Applied Sciences)
The adoption of healthcare technologies has grown significantly, with real-time location systems (RTLSs) gaining particular attention. Despite decades of research, gaps persist in understanding the current state of the field and its future directions. This scoping review, conducted by PRISMA guidelines, identified 1718 articles retrieved from six databases, from which 83 were included. The findings reveal a dominance of U.S.-based case studies and a lack of systematic literature reviews. While RFID is the most commonly used technology, alternative solutions are emerging, though few studies explore their combined use. The emergency department is the most studied setting, focusing on patient flow. However, case study quality varies, which affects replicability, and literature reviews often fail to justify technological choices adequately. RTLS benefits include improved efficiency, enhanced patient safety, and cost reduction, but challenges such as precision issues and signal interference persist. RTLS also serves as a foundation for digital twins, integrating AI and Industry 4.0 technologies for more sustainable healthcare operations. Technological advancements may shift perceptions of RTLS challenges and benefits, highlighting the need for analysis by technology type and release date. Additionally, current MeSH terms fail to adequately cover healthcare technologies, resulting in the exclusion of relevant studies.